Effects of Electronic Cigarettes on Periodontal Health: A Systematic Review and Meta-Analysis - Reem Alkattan; Nada Tashkandi; Amani Mirdad; Hossam Tharwat Ali; Nouf Alshibani; Eman Allam (International Dental Journal)
Objectives: The use of electronic cigarettes “e-cigarettes,” or vaping is growing in popularity, especially among adolescents and young adults. While the effects of cigarette smoking on oral health are well-established, the exact impact that e-cigarettes may have on dental tissues is still uncertain. The aim of the current review was to summarize evidence related to the effect of vaping on the periodontal health status of e-cigarette users. Methods: A comprehensive electronic search was performed using PubMed, Web of Science, and Scopus databases, until January 31st, 2024. Two independent reviewers participated in the screening of studies, data extraction, and assessment of the included studies. Any disagreements were resolved by a third reviewer the quality assessment was done using the Newcastle-Ottawa Scale to assess the risk of bias. A frequentist meta-analysis was performed using R Statistical Software. The random effects model was adopted. Data were described as mean difference (MD) and 95% confidence interval (CI). A p-value of ≤ .05 was deemed statistically significant. Results: Ten studies met the eligibility criteria. Overall, the findings were consistent, with most studies showing that e-cigarette users are at greater risk of periodontal disease than nonsmokers, but that they have a lower risk than cigarette smokers. Pooling results showed lower mean probing depth (PD) among nonsmokers than e-smokers (MD: -1.91; 95% CI: [-3.36: -0.47]; p-value = .01) while it was higher among cigarette smokers in participants with periodontitis (MD:0.43; 95%CI: [0.08:0.79]; p-value = .02). Compared to e-smoking, nonsmokers had lower PI (MD: -20.63; 95%CI: [-28.04: -13.21]; p-value < .001) while cigarette smokers had higher PI (MD: 4.88; 95% CI: [-1.52:11.29]; p-value = .135). Among participants with periodontitis, only cigarette smokers had significantly higher PI (MD: 4.53; 95%CI: [1.94:7.13]; p-value < .001). Conclusion: Based on the current analysis, conventional cigarette smoking is the most detrimental to periodontal health among the groups compared in all included studies. This indicates that traditional cigarettes have a more severe impact on periodontal tissues than do e-cigarettes. The data suggest a gradient of risk where nonsmokers have the lowest risk, e-cigarette users have a moderate risk, and cigarette smokers have the highest risk for periodontal health issues.